2022
DOI: 10.1002/smm2.1142
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructures and catalytic atoms engineering of tellurium‐based materials and their roles in electrochemical energy conversion

Abstract: With the dramatic developments of renewable and environmental‐friendly electrochemical energy conversion systems, there is an urgent need to fabricate durable and efficient electrocatalysts to address the limitation of high overpotentials exceeding thermodynamic requirements to facilitate practical applications. Recently, tellurium‐based nanomaterials (Te NMs) with unique chemical, electronic, and topological properties, including Te‐derived nanostructures and transition metal tellurides (TMTs), have emerged a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 231 publications
0
11
0
Order By: Relevance
“…It has been disclosed that the high electronegative metal catalytic sites in metal oxides would result in poor reversible redox properties when reacting with oxygen intermediates. Recent reports have revealed that cobalt oxides can serve as stable and biocompatible support with a high redox potential of Co 3+ /Co 2+ for diverse biocatalytic therapeutics. Meanwhile, originating from its redox-active characteristics of cobalt oxides, the Co 2+ sites can further contribute electrons (Co 2+ to Co 3+ ) to the metal centers, thus introducing charge transfer between the support materials and active centers. Therefore, loading catalytic atoms on the cobalt oxides and precisely modulating their electronic structures and microenvironments of catalytic centers may offer promising opportunities to construct efficient and cascade ROS-scavenging artificial enzyme systems, while this remains challenging and undiscovered.…”
Section: Introductionmentioning
confidence: 99%
“…It has been disclosed that the high electronegative metal catalytic sites in metal oxides would result in poor reversible redox properties when reacting with oxygen intermediates. Recent reports have revealed that cobalt oxides can serve as stable and biocompatible support with a high redox potential of Co 3+ /Co 2+ for diverse biocatalytic therapeutics. Meanwhile, originating from its redox-active characteristics of cobalt oxides, the Co 2+ sites can further contribute electrons (Co 2+ to Co 3+ ) to the metal centers, thus introducing charge transfer between the support materials and active centers. Therefore, loading catalytic atoms on the cobalt oxides and precisely modulating their electronic structures and microenvironments of catalytic centers may offer promising opportunities to construct efficient and cascade ROS-scavenging artificial enzyme systems, while this remains challenging and undiscovered.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with Pt group metal-based materials, non-noble metal-structured MAECs possess various advantages in electrocatalysis, such as earth-abundance, high-cost performance, and excellent tunable stability. [129][130][131] Thus, developing highly active and stable non-noble metal-structured MAECs has also been a top topic in the field of electrocatalysis. [132] Recently, many non-noble metal-structured MAECs have been put forward, such as FeNi, [133,134] FeCo, [135,136] NiCo, [137,138] and MoNi [139][140][141][142] based alloys.…”
Section: Non-noble Metal-structured Maecs: Merits and Modulationsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Proting from their excellent structure stability and tolerance of different elements, ABO 3 -type perovskites 8 are prospective candidates for the electrode materials of SOCs. 9,10 Since the electrocatalytic activity of the materials' exterior layers is closely associated with catalysis, [11][12][13][14][15] researchers have demonstrated that the activity of the perovskites can be effectively tuned by surface modication, such as decorating metallic nanoparticles on the surface of the perovskite's backbone to increase the concentration of the active sites. 16 Conventionally, ex situ deposition is adopted to prepare the nanoparticle-decorated materials (NDMs).…”
Section: Introductionmentioning
confidence: 99%